PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA KEUANGAN DENGAN PEMBELAJARAN ORGANISASI SEBAGAI VARIABEL MEDIASI - Ellya Oktavia Setiawan; Devie Devie Devie (Business Accounting Review, 2018)
This study aimed to examine the influence of management control system towards financial performance with organizational learning as intervening variable in the registered manufacturing companies located in Surabaya and its surroundings. This study used qualitative approach, obtained from distribution of questionnaires to 33 registered manufacturing companies in Surabaya and sorrounding areas. The data processed by Smart PLS software version 3.0. The result showed positive and significant influence of management control system towards financial performance, positive and significant influence of management control system towards organizational learning, positive and significant influence of organizational learning towards financial performance. Besides, organizational learning proven as mediating variable of management control system towards financial performance.